PENGARUH SISTEM PEMBAYARAN ELEKCTRONIC MONEY TERHADAP KEPUASAN PELANGGAN DI TOKO 257 TANI KABUPATEN SIDENRENG RAPPANG - Zelvi; Andi Riska Andreani Syafaruddin; Mutmainna Cahyani Thahir; Rahman Yakub (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the electronic money payment system on customer satisfaction at Toko 257 Tani, Sidenreng Rappang Regency. The development of digital technology has encouraged the implementation of non-cash payment systems in various sectors, including agriculture-based businesses. Toko 257 Tani has implemented an electronic money payment system to improve transaction efficiency and customer convenience. However, several problems remain, such as low digital literacy, limited understanding of electronic payment mechanisms, and insufficient technical support for customers. This research uses a quantitative approach with a correlational design. The population consisted of 250 customers who used electronic money payment methods at Toko 257 Tani. The sample included 154 respondents selected using accidental sampling. Data were collected through questionnaires, observation, documentation, and literature study. Data analysis used descriptive statistics, validity and reliability testing, and simple linear regression with SPSS. The results indicate that the implementation of electronic money positively influences customer satisfaction. The convenience, efficiency, and speed of digital transactions contribute significantly to improving customer experience. This study provides implications for improving digital payment systems in agricultural retail businesses.